EFFECTIVENESS OF THE EARLY CASE DETECTION SYSTEM (SDDP) IN PREVENTING DISPARITY IN DECISIONS AND SUPPORTING THE PRINCIPLE OF JUDICIAL TRILOGY IN THE BALIGE DISTRICT COURT - Pearl Princila Br. Manurung; Rachmi Sulistyarini; Hamidi Masykur (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study analyzes the effectiveness of the Early Case Detection System (SDDP) integrated into the Case Tracking Information System (SIPP) as an instrument to prevent disparity in decisions in civil cases in the general court environment. The focus of the study is directed at the implementation of SDDP at the Balige District Court as a representation of the implementation of electronic court technology ( e-court ) in the case handling process. This study uses a juridical-empirical method with a sociological approach to examine the relationship between the electronic court system and the objectives of the court in the Trilogy of Justice: simple, fast, and low cost. The research results indicate that the SDDP has not been effective. This is due to the absence of regulations mandating its use, low technical understanding among judicial officials, and the suboptimal quality of data in the SIPP, which hinders the ability to detect cases with similar subjects, objects, and legal relationships. This study concludes that the SDDP has significant potential to increase legal certainty and prevent conflicting decisions, but regulatory improvements, technical competency, and system updates are needed to achieve maximum effectiveness.